English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(-3x^3 y^5)^3
__________
(9x^2 y)^2

2007-01-26 07:31:34 · 7 answers · asked by Olivia 4 in Science & Mathematics Mathematics

7 answers

Simplify > [(-3x^3y^5)^3] / [(9x^2y)^2]

First: place the exponents to each term and variable in parenthesis > when you have a variable with an exponent & raised to another exponent, add the exponents...

[-3^3 x^(3*3) y^(5*3)] / [(9^2 x^(2*2) y^2)]

[(-3)(-3)(-3) x^9y^15] / [(9)(9) x^4y^2]

[(-3)(9)x^9y^15] / [81x^4y^2]

[- 27x^9y^15] / [81x^4y^2]

Sec: simplify the coefficients & variables...

(-27/81)(x^9/x^4)(y^15/y^2

= (- x^5y^13)/3

2007-01-26 15:18:58 · answer #1 · answered by ♪♥Annie♥♪ 6 · 3 0

The numerator first...
(ab)^3= a^3*b^3, e.g. (2*3)^3= 2*2*2*3*3*3=8*27=216= 6^3
Also, (a^b)^c= a^bc, e.g. (2^3)^2= 2^6= 64= 8^2

(-3(x^3)y^5)^3= [-3(x^3)]^3 * (y^5)^3]
= (-3)^3 * (x^3)^3 * (y^5)^3
= -27 * x^9 * y^15
= -27(x^9)(y^15)

Now the denominator,

(9(x)^2*y)^2
= (9(x)^2)^2 * y^2
= 81*x^4 * y^2
= 81(x^4)(y^2)

Taking the quotient/ ratio of these gives:

-27(x^9)(y^15) / 81(x^4)(y^2)
= (-27/81)*{(x^9)/(x^4)}*[(y^15)/(y^2)]

Now we know that (x^a)/(x^b)= x^(a-b), e.g. 2^3/2^2=2^1

Therefore your answer is

(-1/3)*(x^5)*(y^13)

To check that this works, let x=5 and y=2
Our solution is (-1/3)*5*5*5*5*5*2*2*2*2*2*2*2*2*2*2*2*2*2
=(-1/3)*3125*8192=-8533333.33

The question would be
(-3*5*5*5*2*2*2*2*2)*(-3*5*5*5*2*2*2*2*2)*(-3*5*5*5*2*2*2*2*2)
__________
(9*5*5*2)*(9*5*5*2)
=- 1728000000000/202500= -8533333.3333, as above. I hope this numerical proof will aid your understanding of the algebra.

2007-01-26 08:08:52 · answer #2 · answered by samuelll 2 · 3 0

Everthing in the ()gets raised (multiply exponents)

(-3)^3 x^9 y^15
--------------------
9^2 x^4 y^2

-27x^9y^15
---------------
81x^4 y^2

- (x^5 y^13)
------------
3

2007-01-26 07:44:35 · answer #3 · answered by math_teacher_02 2 · 3 0

(-3x^3 y^5)^3
= (-3)^3 (x^3)^3 (y^5)^3
= -27x^9 y^15

(9x^2 y)^2
= 9^2 (x^2)^2 y^2
= 81x^4 y^2

You have
-27x^9 y^15 / (81x^4 y^2)
= -x^5 y^13 / 3

2007-01-26 07:35:29 · answer #4 · answered by MsMath 7 · 5 1

Ok, seriously, 18 QUESTIONS IN THE LAST 5 HOURS?! Do your OWN freaking homework! People like you tick me off. You can't expect people to just do your homework for you the rest of your life, can you? If you really need this much help, go ask your teacher. Jeez!

2007-01-26 09:30:13 · answer #5 · answered by lil e 2 · 3 1

- x^5 y^13
-------------
12
Unless I misplaced something.

2007-01-26 07:48:17 · answer #6 · answered by sparbles 5 · 3 1

Erase it.

2007-01-26 07:38:52 · answer #7 · answered by crabskulls 2 · 2 1

fedest.com, questions and answers